A two-dimensional molybdenum titanium carbide humidity sensitive material and its preparation method and application

By using two-dimensional molybdenum carbide as a humidity-sensitive material, its water adsorption performance is improved through etching and intercalation processing, the problem of low sensitivity of existing humidity sensors in a wide humidity range is solved, and a high sensitivity and fast response humidity sensor is achieved.

CN115266834BActive Publication Date: 2025-02-28EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210876574.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-25
Publication Date
2025-02-28
Estimated Expiration
2042-07-25

AI Technical Summary

Technical Problem

The existing resistive humidity sensors have poor sensitivity over a wide humidity range, long response time, poor linearity, and low accuracy at high and low humidity.

Method used

Two-dimensional molybdenum carbide is used as a humidity-sensitive material. By etching molybdenum titanium aluminum carbide in hydrofluoric acid, a multi-layer molybdenum carbide is obtained, and then tetramethyl ammonium hydroxide solution is added for treatment, increasing the spacing of the layer and specific surface area, thereby increasing the water adsorption capacity and adsorption rate.

Benefits of technology

A humidity sensor with high sensitivity and fast response time in the relative humidity range of 3.2 to 92.7% is achieved, and good stability is maintained within a wide humidity range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115266834B_ABST
    Figure CN115266834B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of humidity sensitive sensors and provides a two-dimensional molybdenum titanium carbide (Mo2TiC2T x ) humidity sensitive material and its preparation method and application. The present invention uses molybdenum titanium aluminum carbide (Mo2AlTiC2) as an etching raw material to achieve two-dimensional titanium carbide (Ti3C2T x ) part of the Ti atoms are replaced by Mo atoms; then the etched molybdenum titanium carbide is etched using tetramethylammonium hydroxide (C4H 13 NO) is layered to form two-dimensional molybdenum titanium carbide. The Mo atom promotes the water adsorption kinetics of the two-dimensional molybdenum titanium carbide, and the layering increases the specific surface area of ​​the material, which ultimately leads to a larger water adsorption capacity and adsorption rate of the material. When the two-dimensional molybdenum titanium carbide prepared by the present invention is used as a humidity sensitive material in a humidity sensor, the obtained humidity sensor exhibits ultra-high sensitivity, small humidity hysteresis and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of humidity sensitive sensors, and in particular to a two-dimensional molybdenum titanium carbide humidity sensitive material and a preparation method and application thereof. Background Art

[0002] Humidity is a physical quantity that characterizes the concentration of water vapor in the air. The detection of humidity is very important in the fields of environmental monitoring, industrial and agricultural production, library and archive management, and meteorological observation. Humidity sensors are electronic devices that can convert water vapor content into visual quantities, among which humidity-sensitive materials play a decisive role in sensor performance.

[0003] Common types of humidity sensors are divided into electrical, acoustic and optical types. Among them, electrical humidity sensors have the advantages of small size, simple design and flexible process, and resistive humidity sensors under the electrical type are commonly used humidity sensors due to their low manufacturing cost. An ideal resistive humidity sensor should have high sensitivity, long-term stability, wide detection limit and fast response time, while traditional resistive humidity sensors have shortcomings such as long response time, poor linearity, low accuracy at high and low humidity and wide hysteresis. In recent years, with the emergence of emerging two-dimensional transition metal carbides / nitrides (collectively referred to as MXenes) with the advantages of adjustable surface properties, adjustable band gap, excellent electrical properties and controllable interlayer spacing, the sensitivity and comprehensive performance of resistive humidity sensors prepared by them are expected to be improved to a certain extent.

[0004] At present, some studies have used two-dimensional titanium carbide as a humidity-sensitive material to prepare resistive humidity sensors. Although the sensitivity of the humidity sensors obtained has been improved compared with before, their sensitivity is still poor within a wider humidity range.

[0005] Therefore, there is an urgent need to provide a method for preparing a humidity sensitive material with high sensitivity. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a two-dimensional molybdenum titanium carbide humidity sensitive material and its preparation method and application. The humidity sensor prepared using the two-dimensional molybdenum titanium carbide humidity sensitive material provided by the present invention has high sensitivity and still has good stability in a wide relative humidity range of 3.2 to 92.7%.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a two-dimensional molybdenum titanium carbide humidity sensitive material, comprising the following steps:

[0009] (1) adding molybdenum-titanium-aluminum carbide to hydrofluoric acid for etching, and then sequentially performing a first centrifugation and a first washing to obtain a multilayer molybdenum-titanium carbide precipitate;

[0010] (2) Adding tetramethylammonium hydroxide solution to the multilayer molybdenum titanium carbide precipitate obtained in step (1), and then stirring, centrifuging, washing and filtering are performed in sequence to obtain a two-dimensional molybdenum titanium carbide humidity sensitive material.

[0011] Preferably, the mass ratio of molybdenum titanium aluminum carbide to hydrofluoric acid in step (1) is 1 g: (15-25) mL.

[0012] Preferably, the mass concentration of the hydrofluoric acid in step (1) is 45-55%.

[0013] Preferably, the pH value of the product after the first washing in step (1) is 6-7.

[0014] Preferably, the etching temperature in step (1) is 50-60° C., and the etching time is 40-60 h.

[0015] Preferably, the mass concentration of the tetramethylammonium hydroxide solution in step (2) is 20-30%.

[0016] The present invention provides a two-dimensional molybdenum titanium carbide humidity sensitive material prepared by the preparation method described in the above scheme, and the two-dimensional molybdenum titanium carbide humidity sensitive material is a two-dimensional molybdenum titanium carbide nanosheet.

[0017] The present invention also provides an application of the two-dimensional molybdenum titanium carbide humidity sensitive material described in the above scheme in a humidity sensor, wherein the two-dimensional molybdenum titanium carbide suspension is drop-coated on a sensor chip, and after drying, it is assembled in a sensor circuit to obtain a humidity sensor based on two-dimensional molybdenum titanium carbide; wherein the two-dimensional molybdenum titanium carbide suspension is an upper layer liquid obtained by mixing two-dimensional molybdenum titanium carbide and deionized water and subjecting to a third centrifugation.

[0018] Preferably, the concentration of the two-dimensional molybdenum titanium carbide suspension is 3-8 mg / mL.

[0019] Preferably, the sensor chip is composed of an aluminum oxide (Al2O3) sheet with Pt interdigital electrodes.

[0020] The present invention provides a method for preparing a two-dimensional molybdenum titanium carbide humidity sensitive material, comprising the following steps: (1) adding molybdenum titanium aluminum carbide to hydrofluoric acid for etching, and then sequentially performing a first centrifugation and a first washing to obtain a multilayer molybdenum titanium carbide precipitate; (2) adding a tetramethylammonium hydroxide solution to the multilayer molybdenum titanium carbide precipitate obtained in step (1), and then sequentially performing stirring, a second centrifugation, a second washing and suction filtration to obtain a two-dimensional molybdenum titanium carbide humidity sensitive material. The present invention uses molybdenum titanium aluminum carbide as an etching raw material, thereby partially replacing the outer layer Ti atoms of titanium carbide with Mo atoms to obtain molybdenum titanium carbide, and the Mo atoms promote the water adsorption kinetics of molybdenum titanium carbide; at the same time, the present invention adds tetramethylammonium hydroxide during the preparation of the two-dimensional molybdenum titanium carbide, and the tetramethylammonium hydroxide can be used as an intercalation agent to enter the interlayer of the multilayer molybdenum titanium carbide, and the interlayer spacing is increased by intercalation, and the interlayer force is weakened to achieve stratification, and the stratification can increase the specific surface area of ​​the material, and further increase the water adsorption capacity and adsorption rate of the two-dimensional molybdenum titanium carbide. Experimental results show that the humidity sensor based on two-dimensional molybdenum titanium carbide obtained by the method provided by the present invention has fast response time, excellent humidity selectivity and no hysteresis characteristics, while maintaining good stability in a wide relative humidity range of 3.2 to 92.7%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of air humidity detection when the two-dimensional molybdenum titanium carbide humidity-sensitive material prepared in Example 1 of the present invention is applied to a humidity sensor;

[0022] Figure 2 X-ray diffraction (XRD) patterns of two-dimensional Mo2TiC2 and Ti3C2 prepared in step (2) of Example 1 of the present invention and step (2) of Comparative Example 2, respectively;

[0023] Figure 3 A dynamic resistance change diagram when the two-dimensional molybdenum titanium carbide prepared in Example 1 of the present invention is applied to a humidity sensor and when the two-dimensional titanium carbide prepared in Comparative Example 1 is applied to a humidity sensor;

[0024] Figure 4 A resistance change diagram of the two-dimensional molybdenum titanium carbide prepared in Example 1 of the present invention when applied to a humidity sensor and a two-dimensional titanium carbide prepared in Comparative Example 1 when applied to a humidity sensor during the response and recovery process;

[0025] Figure 5 This is a stability test chart of the two-dimensional molybdenum titanium carbide prepared in Example 1 of the present invention when applied to a humidity sensor. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a two-dimensional molybdenum titanium carbide humidity sensitive material, comprising the following steps:

[0027] (1) adding molybdenum-titanium-aluminum carbide to hydrofluoric acid for etching, and then sequentially performing a first centrifugation and a first washing to obtain a multilayer molybdenum-titanium carbide precipitate;

[0028] (2) Adding tetramethylammonium hydroxide solution to the multilayer molybdenum titanium carbide precipitate obtained in step (1), and then stirring, centrifuging, washing and filtering are performed in sequence to obtain a two-dimensional molybdenum titanium carbide humidity sensitive material.

[0029] The present invention adds molybdenum-titanium-aluminum carbide into hydrofluoric acid for etching, and then sequentially performs a first centrifugation and a first washing to obtain a multilayer molybdenum-titanium carbide precipitate.

[0030] The present invention has no special provisions on the source of the molybdenum-titanium-aluminum carbide, and conventional commercial products can be used.

[0031] In the present invention, the mass concentration of the hydrofluoric acid is preferably 45-55%, more preferably 50%. In the present invention, the mass ratio of the molybdenum-titanium-aluminum carbide to the volume ratio of the hydrofluoric acid is preferably 1 g: (15-25) mL, more preferably 1 g: 20 mL. The mass concentration of the hydrofluoric acid and the amount of the molybdenum-titanium-aluminum carbide and the hydrofluoric acid are controlled within the above ranges in order to achieve sufficient etching of the molybdenum-titanium-aluminum carbide by the hydrofluoric acid.

[0032] In the present invention, the etching temperature is preferably 50-60°C, more preferably 55°C; the etching time is preferably 40-60h, more preferably 48h. The present invention limits the etching temperature and time to the above range, which is conducive to achieving sufficient etching of molybdenum titanium carbide by hydrofluoric acid.

[0033] In the present invention, the etching is preferably carried out under stirring conditions. In the present invention, the stirring rate is preferably 400-600 rpm, more preferably 500 rpm. The present invention controls the stirring rate within the above range in order to achieve full contact between hydrofluoric acid and molybdenum-titanium-aluminum-carbide, thereby achieving full etching of molybdenum-titanium-aluminum-carbide.

[0034] The present invention preferably slowly adds molybdenum titanium aluminum carbide to hydrofluoric acid for etching. The present invention has no special provisions for the rate of slow addition, and it can be carried out according to the routine known to those skilled in the art. The present invention slowly adds molybdenum titanium aluminum carbide to hydrofluoric acid, mainly to avoid violent reaction and liquid splashing during etching, and to improve the safety of operation.

[0035] The present invention has no special provisions for the operation of the first centrifugation, and the solid-liquid separation can be achieved by a centrifugation method well known to those skilled in the art. The present invention obtains the etched solid by the first centrifugation. The present invention has no special provisions for the rate of the first centrifugation, and it can be selected according to the routine. In the present invention, the reagent for the first centrifugation washing is preferably deionized water.

[0036] The present invention has no special provisions for the first washing method. The washing method well known to those skilled in the art can be used to wash away the hydrofluoric acid on the solid product after centrifugation with deionized water. In the present invention, the pH value of the product after the first washing is preferably 6 to 7. Because the pH value of molybdenum titanium carbide itself is neutral, after washing away the hydrofluoric acid adhering to it, since the hydrofluoric acid cannot be completely removed, the pH of the washed solid product is close to neutral or slightly acidic.

[0037] After obtaining the multilayer molybdenum titanium carbide, the present invention adds a tetramethylammonium hydroxide solution to the multilayer molybdenum titanium carbide precipitate, and then sequentially performs stirring, a second centrifugation, a second washing and suction filtration to obtain a two-dimensional molybdenum titanium carbide humidity sensitive material.

[0038] In the present invention, the mass concentration of the tetramethylammonium hydroxide solution is preferably 20-30%, more preferably 25%. In the present invention, the volume of the tetramethylammonium hydroxide solution is preferably 20-40mL, more preferably 30mL. In the present invention, tetramethylammonium hydroxide is used as an intercalation agent to enter the multilayer molybdenum titanium carbide layer, and the intercalation increases the interlamellar spacing and weakens the interlamellar force to achieve stratification. After washing away the intercalation agent, a two-dimensional molybdenum titanium carbide suspension is obtained, and the specific surface area is increased by stratification, further increasing the water adsorption capacity and adsorption rate of the two-dimensional molybdenum titanium carbide. The present invention controls the concentration and dosage of the tetramethylammonium hydroxide solution within the above range, which is more conducive to obtaining two-dimensional molybdenum titanium carbide.

[0039] The present invention has no special provisions for the stirring rate, and a conventional selection can be used. In the present invention, the stirring time is preferably 10 to 15 hours, and more preferably 12 hours. The present invention limits the stirring time to the above range, so that tetramethylammonium hydroxide can be used as an intercalation agent to fully enter the multilayer molybdenum titanium carbide layer.

[0040] The present invention has no special provisions for the operation of the second centrifugation, and a centrifugation method well known to those skilled in the art can be used. The present invention has no special provisions for the speed and time of the second centrifugation, and conventional methods can be used. The present invention washes tetramethylammonium hydroxide from the two-dimensional molybdenum titanium carbide by the second centrifugal washing.

[0041] The present invention has no special provisions for the second washing method, and the impurities remaining on the solid can be removed by a washing method well known to those skilled in the art. In the present invention, the reagent for the second washing is preferably deionized water. The present invention further removes the tetramethylammonium hydroxide remaining on the two-dimensional molybdenum titanium carbide through the second washing.

[0042] The present invention has no special provisions on the method of suction filtration, and solid-liquid separation can be achieved by suction filtration methods well known to those skilled in the art.

[0043] The present invention provides a preparation method of a humidity-sensitive material based on two-dimensional molybdenum titanium carbide. By using molybdenum titanium aluminum carbide as an etching raw material, part of the outer-layer Ti atoms of titanium carbide are replaced by Mo atoms to obtain molybdenum titanium carbide. The Mo atoms promote the water adsorption kinetics of the molybdenum titanium carbide. At the same time, in the process of preparing the two-dimensional molybdenum titanium carbide, the present invention adds tetramethylammonium hydroxide. The tetramethylammonium hydroxide can be used as an intercalator to enter between multiple layers of molybdenum titanium carbide. The intercalation increases the interlamellar spacing and weakens the interlamellar force to achieve stratification. The stratification can increase the specific surface area of ​​the material, and further increase the water adsorption capacity and adsorption rate of the two-dimensional molybdenum titanium carbide.

[0044] The present invention provides a two-dimensional molybdenum titanium carbide humidity sensitive material prepared by the preparation method described in the above scheme, and the two-dimensional molybdenum titanium carbide humidity sensitive material is a two-dimensional molybdenum titanium carbide nanosheet.

[0045] The present invention also provides the use of the two-dimensional molybdenum titanium carbide humidity sensitive material described in the above scheme in a humidity sensor.

[0046] In the present invention, the application is preferably to drop the two-dimensional molybdenum titanium carbide suspension onto a sensor chip, and then assemble it into a sensor circuit after drying to obtain a humidity sensor based on two-dimensional molybdenum titanium carbide.

[0047] In the present invention, the two-dimensional molybdenum titanium carbide suspension is preferably an upper layer liquid obtained by mixing two-dimensional molybdenum titanium carbide and deionized water and subjecting the mixture to a third centrifugation.

[0048] In the present invention, the concentration of the two-dimensional molybdenum titanium carbide suspension is 3 to 8 mg / mL, more preferably 5 mg / mL. In the present invention, the amount of the two-dimensional molybdenum titanium carbide suspension is preferably 150 to 250 μL, more preferably 200 μL. The present invention limits the concentration and amount of the two-dimensional molybdenum titanium carbide suspension to the above range, and the comprehensive performance of the obtained humidity sensor is better.

[0049] The present invention has no special provisions on the rate and time of the third centrifugation, and conventional selections are sufficient. The present invention obtains a uniformly dispersed suspension through the third centrifugation.

[0050] The present invention has no special provisions for the drip coating method, and the sensor chip can be uniformly coated by dripping the two-dimensional molybdenum titanium carbide suspension in a conventional manner.

[0051] The present invention has no special provisions on the drying temperature and time, and it is sufficient to remove the moisture on the sensor chip without causing damage to the chip itself.

[0052] In the present invention, the sensor chip is preferably composed of a platinum (Pt) interdigital electrode circuit printed on an aluminum oxide (Al2O3) substrate. The present invention has no special provisions on the source of the sensor chip, and any conventional commercially available one can be used.

[0053] The present invention has no special provisions on the source of the sensor circuit, and conventional commercially available products can be selected.

[0054] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Example 1

[0056] The preparation method of the two-dimensional molybdenum titanium carbide humidity sensitive material in this embodiment comprises the following steps:

[0057] (1) slowly adding molybdenum-titanium-aluminum carbide into hydrofluoric acid, etching under stirring conditions, and then sequentially performing a first centrifugation and a first washing to obtain a multilayer molybdenum-titanium carbide precipitate;

[0058] The mass concentration of hydrofluoric acid is 50%; the mass ratio of molybdenum titanium aluminum carbide to hydrofluoric acid is 1g:20mL; the pH value of the product after the first washing is about 6; the etching temperature is 55°C and the time is 48h; the stirring rate is 500rpm; the first centrifugation rate is 3500rpm and the time is 5min; the first washing reagent is deionized water;

[0059] (2) adding a tetramethylammonium hydroxide solution to the multilayer molybdenum titanium carbide precipitate obtained in step (1), and then stirring, centrifuging, washing and filtering in sequence to obtain a two-dimensional molybdenum titanium carbide humidity sensitive material;

[0060] Among them, two-dimensional molybdenum titanium carbide is Mo2TiC2T x express;

[0061] The mass concentration of tetramethylammonium hydroxide solution is 25%, and the dosage is 30 mL; stirring is carried out at room temperature for 12 hours; the speed of the second centrifugation is 8500 rpm, and the time is 5 minutes; the reagent for the second washing is deionized water.

[0062] Application of the two-dimensional molybdenum titanium carbide humidity sensitive material prepared in Example 1 in a humidity sensor,

[0063] The two-dimensional molybdenum titanium carbide suspension prepared in Example 1 is drop-coated on the sensor chip, and after drying, it is assembled in the sensor circuit to obtain a humidity sensor based on the two-dimensional molybdenum titanium carbide;

[0064] Among them, the two-dimensional molybdenum titanium carbide suspension is an upper layer liquid obtained by mixing two-dimensional molybdenum titanium carbide and deionized water and subjecting to the third centrifugation; the concentration of the two-dimensional molybdenum titanium carbide suspension is 5 mg / mL, and the dosage is 200 μL; the sensor chip is composed of an alumina (Al2O3) sheet with a Pt interdigital electrode; the drying temperature is 50°C, and the time is 15 min; the sensor chip was purchased from Wuhan Huachuang Ruike Technology Co., Ltd., model four-channel material gas sensitive performance tester chip.

[0065] Comparative Example 1

[0066] In this embodiment, two-dimensional titanium carbide is prepared and applied to a humidity sensor, wherein the preparation method and application of the two-dimensional titanium carbide are the same as those in Embodiment 1, with the only difference being that the raw material molybdenum titanium aluminum carbide in step (1) is changed to titanium aluminum carbide, wherein step (2) obtains two-dimensional titanium carbide and is represented by Ti3C2.

[0067] The operation process of using the humidity sensor based on two-dimensional molybdenum titanium carbide prepared in Example 1 of the present invention to detect air humidity is shown in Figure 1 .from Figure 1 It can be seen that the gas is input into the airflow control module through the gas cylinder in the gas cylinder cabinet, and then the gas is output to the gas washing bottle. The humidity sensor based on two-dimensional molybdenum carbide prepared in Example 1 obtains the signal input, and then outputs the signal to the computer, and the computer provides the working voltage of the sensor.

[0068] The above-mentioned specific process is: gas is introduced from the gas cylinder into the airflow control module, passed into the washing bottle filled with deionized water, and humid air is obtained by bubbling. The humid air flows into the sensor test cavity of the humidity sensor through the control module; the increase of humidity in the test cavity is achieved by the introduced humid air, and the reduction of humidity is achieved by introducing inert gases such as Ar into the test cavity to drive away the humid air; the computer is connected to the sensor to provide the voltage required by the sensor, and the result is output to the computer through the signal amplifier.

[0069] For the humidity sensor based on two-dimensional molybdenum carbide titanium prepared in Example 1 of the present invention, the output variable is the resistance change, and the input is the initial resistance; the response time refers to the time from the sensor element contacting the target to reach a stable indication value under test conditions; usually, the time to reach 90% of the stable value is read as the response time; hysteresis refers to the different response times of the humidity sensitive device under moisture absorption and dehumidification conditions.

[0070] 1. X-ray diffraction was performed on the two-dimensional Mo2TiC2 and Ti3C2 prepared in step (2) of Example 1 and step (2) of Comparative Example 2, and the obtained X-ray diffraction pattern (XRD) was shown in Figure 2 .from Figure 2 It can be seen that both Mo2TiC2 and Ti3C2 have diffraction peaks at 5-10°, proving that the Mo2TiC2 and Ti3C2 materials were successfully synthesized.

[0071] 2. The humidity sensor based on two-dimensional molybdenum titanium carbide of Example 1 and the humidity sensor based on two-dimensional titanium carbide of Comparative Example 1 were tested for dynamic resistance change. The test results are shown in Figure 3 .from Figure 3 It can be seen that from low humidity to high humidity 3.2-92.7%, 3.2-50.2%, 3.2-19.3%, the resistance change of the humidity sensor based on two-dimensional molybdenum carbide titanium in Example 1 is higher than that of Comparative Example 1, indicating that the sensitivity of the humidity sensor based on two-dimensional molybdenum carbide titanium in Example 1 is much higher than that of the humidity sensor based on two-dimensional titanium carbide in Comparative Example 1, and the response time is also faster than that of the humidity sensor based on two-dimensional titanium carbide. Among them, the calculation of sensitivity is the ratio of the resistance change to the initial resistance; the calculation of response time is the time required for the resistance to change by 90%.

[0072] 3. The corresponding resistance changes under different relative humidity during the response and recovery process of the humidity sensor based on two-dimensional molybdenum titanium carbide in Example 1 are shown in Figure 4 .from Figure 4 It can be seen that the resistances corresponding to different relative humidities during the response and recovery processes are substantially consistent, indicating that the humidity sensor of Example 1 has no obvious hysteresis phenomenon.

[0073] 4. The humidity sensor based on two-dimensional molybdenum titanium carbide of Example 1 was tested five times from low humidity to high humidity. The test results are shown in Figure 5 .from Figure 5 It can be seen that the humidity sensor of Example 1 maintains good repeatability, indicating that the humidity sensor provided by the present invention has good stability.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a two-dimensional molybdenum titanium carbide humidity sensitive material, comprising the following steps: (1) adding molybdenum-titanium-aluminum carbide to hydrofluoric acid for etching, and then sequentially performing a first centrifugation and a first washing to obtain a multilayer molybdenum-titanium carbide precipitate; (2) adding a tetramethylammonium hydroxide solution to the multilayer molybdenum titanium carbide precipitate obtained in step (1), and then stirring, centrifuging, washing and filtering in sequence to obtain a two-dimensional molybdenum titanium carbide humidity sensitive material; The mass ratio of molybdenum titanium aluminum carbide to hydrofluoric acid in step (1) is 1 g: (15-25) mL; The mass concentration of hydrofluoric acid in step (1) is 45-55%; The pH value of the product after the first washing in step (1) is 6 to 7; The etching temperature in step (1) is 50-60° C. and the etching time is 40-60 h. The mass concentration of the tetramethylammonium hydroxide solution in step (2) is 20-30%.

2. The two-dimensional molybdenum titanium carbide humidity sensitive material prepared by the preparation method of claim 1, characterized in that: The two-dimensional molybdenum titanium carbide humidity sensitive material is a two-dimensional molybdenum titanium carbide nanosheet.

3. Application of the two-dimensional molybdenum titanium carbide humidity sensitive material according to claim 2 in a humidity sensor, characterized in that: The two-dimensional molybdenum titanium carbide suspension is drop-coated on a sensor chip, and after drying, it is assembled in a sensor circuit to obtain a humidity sensor based on the two-dimensional molybdenum titanium carbide; The two-dimensional molybdenum titanium carbide suspension is an upper layer liquid obtained by mixing two-dimensional molybdenum titanium carbide and deionized water and subjecting the mixture to a third centrifugation.

4. The use according to claim 3, characterized in that: The concentration of the two-dimensional molybdenum titanium carbide suspension is 3-8 mg / mL.

5. The use according to claim 3, characterized in that: The sensor chip is composed of a platinum interdigital electrode circuit printed on an alumina substrate.

Citation Information

Patent Citations

  • Preparation method of electrochemical biosensor constructed based on iron-doped two-dimensional nano material

    CN106124589A

  • Two-mode humidity sensor and preparation method thereof

    CN107179337A